Concept Content and Structure of Self-Educational Competence of School Students in the Modern Educational Space - Iryna Maistriuk; Nataliia Ponomarova (Educational Challenges)
Purpose is to characterize the self-educational competence of the individual as a key one in the modern educational space and to reveal the essence and distinguish the structural components of the self-educational competence of school students.